BULLYING PREVENTION IN DIGITAL EDUCATIONAL ENVIRONMENT: STATUS AND WAYS TO IMPROVE - Shakhrai, Valentyna (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article focuses on one of the leading socio-educational problems – the prevention of bullying, because it causes negative moral, emotional, and physical consequences for a significant part of the participants in the educational process. The purpose of the article is to clarify the state of the school and family's ability to prevent bullying and cyberbullying (bullying in the digital educational environment) and to determine the main ways to prevent this negative phenomenon. Research methods: analysis of scientific and methodical literature on the research problem; surveying students, teachers, parents; observation of student behaviour; comparison of the obtained data, their analysis and generalization. The criteria for measuring the effectiveness of pedagogical actions to prevent bullying in the digital educational environment are defined: 1) the ability of teachers to prevent signs of bullying and cyberbullying among students; 2) students' development of social-emotional skills and their ability to resist bullying; 3) pedagogical culture of parents. The levels of bullying prevention in the digital educational environment are characterized: high (socially harmonious); average (socially acceptable); low (social-inhibitory) and defined state of bullying prevention in the modern digital educational environment. It was established that the low (socially inhibiting) level of bullying prevention in the digital educational environment is quite significant. It is proposed to implement a comprehensive educational approach into educational practice, which includes the following components: involvement of various interested parties in the process of preventing and overcoming bullying and cyberbullying; paying special attention to the safety of the educational environment; formation of a positive school climate (class climate); education of vitality of students; establishment of proper interaction between the educational institution and the family, etc. It was concluded that the prevention of bullying and cyberbullying in an educational institution requires systematic work and the use, first of all, of educational tools. Comparing the results of scientific research with the ideas and views of researchers highlighting similar problems confirms the relevance of the research and the feasibility of our proposed approaches to preventing bullying in a digital educational environment. The scientific novelty of the study consists in clarifying the tools for determining the state of bullying prevention in the digital educational environment and outlining the main components of bullying prevention. The article will be useful for scientists, practicing teachers, students of institutions of higher pedagogical education.